Pre-service language teachers' resistance to teacher trainer advice on task design for video-mediated L2 interaction. Issue 2 (3rd April 2022) - Badem-Korkmaz, Fatma; Ekin, Semih; Balaman, Ufuk
ABSTRACT: In pre-service language teacher education contexts, it is challenging to provide hands-on training on task design for technology-mediated settings. This study presents insights from language teacher education activities that aim to tackle this challenge with a multi-step approach consisting of (1) pre-service teachers' collaborative task design conversations in groups, (2) whole-class feedback sessions, (3) implementation of the tasks by actual L2 learners via video-mediated interaction, and (4) pre-service teachers' reflective practices based on the recordings of video-mediated task implementations. We present two cases across these multi-step activities by closely examining the teacher training classroom interactions using Conversation Analysis and also by drawing on the written task design sheets and reflections on video-mediated interactions. More specifically, we document the central role that pre-service teachers' resistance to teacher trainer advice plays in displaying and defending their knowledge about the technological and pedagogical aspects of their task design. We conclude that resistance practices create multiple teacher learning opportunities and maximise space for pre-service teachers' displays of knowledge about task design for video-mediated L2 interactions.